Varamiento de Cetáceos en la costa sur del Perú (2016-2021) - Pizarro-Neyra, José (2022)
Twenty stranding events of cetaceans are reported in four places of southern coast at Peru: Mejía (Arequipa), Punta Coles (Moquegua) and the sites of Ite, Llostay and Los Palos (Tacna). Observations of these events were carried out during 2016-2021. Identified species are: Balaenoptera musculus, Megaptera novaeangliae, Tursiops truncatus, Delphinus delphis, Phocoena spinipinnis, and Lagenorhynchus obscurus. The identification was made using a key of skulls and performing standard morphometric measurements in freshly beached whole animals. Mysticeti's weight was also estimated. Observations included information about clues of interaction between fisheries and cetaceans. Strandings of Mysticeti only occurred in Los Palos, while the species with more landings was Phocoena spinipinnis. Precisely, in the present work, remains of this species are reported for Mejía, Ite, and Los Palos.